'They think we are delaying their outputs' - The challenges of interdisciplinary research: understanding power dynamics between social and biophysical scientists in international crop breeding teams - Cullen, Beth; Snyder, Katherine A.; Rubin, Deborah; Tufan, Hale Ann (Frontiers Media, 2023)
Public sector crop improvement for development programmes aims to produce varieties tailored to the needs of smallholder farmers and their environments. Understanding how social heterogeneity, including gender, drives trait preferences is essential to ensure that crop improvement objectives meet farmers’ and stakeholder demands. This requires an interdisciplinary approach, integrating social science knowledge with crop breeding. Although the necessity of interdisciplinary research is recognised and promoted, it is impeded by a multitude of challenges including ontological and epistemological differences, institutional and global hierarchies, disciplinary power relations and struggles for scientific authority. The Agricultural Research for Development (AR4D) sector is marked by entrenched power differentials, including dominance of the biophysical sciences, a historical emphasis on technical solutions which ignores social contexts, and the underrepresentation of women scientists and farmers themselves. Nevertheless, there is limited theoretically informed analysis of power dynamics within AR4D settings. Drawing on qualitative, ethnographic observations of the Feed the Future Innovation Lab for Crop Improvement (ILCI), this article seeks to understand how power affects interdisciplinary research processes. Critical ethnography and power theory is used to analyse power within international crop breeding collaborations and the implications for inclusive knowledge production and research impact. The Powercube is used to examine how visible, hidden and invisible forms of power manifest within local, national, and international relationships across closed, invited and claimed spaces. Our findings suggest that these intersecting power dimensions, which include disciplinary, gendered, institutional and global hierarchies, constrain the contributions that individual researchers can make – particularly social scientists – thereby hindering disciplinary integration. The ILCI case study reveals the complex multi-dimensional dynamics that emerge within agricultural research teams and highlights structural limitations constraining efforts to build socially inclusive and gender-responsive crop improvement programmes. The article contributes to a small but growing literature studying the social construction of agricultural science, and provides insights that can enable interdisciplinary research strategies to more effectively meet the needs of farmers and other stakeholders.